Historia żółtej ciżemki – architectural space seen through the child’s eye - Świt-Jankowska, Barbara (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
This article focuses on the interdependencies between the film images and architectural education of the youngest. The author has attempted to define what sort of background preconditions the film image to gain the status of a source for psychoeducation, with particular emphasis placed on spatial education. The article includes a case study of Sylwester Chęciński’s film: Historia żółtej ciżemki [The Story of a Yellow Crakow] (1962).